PERAN PEMUDA DALAM MEMINIMALISIR DISKRIMINASI PENDIDIKAN MASYARAKAT TERPENCIL (SD INPRES 5 BAHONG LANGI, DESA BONTO JAI, KECAMATAN BONTO CANI, KABUPATEN BONE) - Dina Islamiah; Anita Anita; Fitriani Fitriani; Irmayanti Irmayanti (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2022)
Education is a pillar that is so important for the future of every circle, both for people who live in cities and people who live in remote villages. Therefore, equal distribution of education by the government is very necessary. But in reality, decent and quality education is still not fully available for all circles. This study aims to find out and describe the education management system of remote communities and the management of the education system at SD Inpres 5 Bahong Langi, Bonto Cani Village, Bonto Jai District, Bone Regency, as well as to find out and describe how the role or contribution of youth in minimizing educational discrimination, especially in remote communities. The research design used in this study is a type of descriptive qualitative research. The results of this study show that the education system of remote communities is very far behind when compared to other regions. The management of the education system applied to SD Inpres 5 Bahong Langi is to implement a learning process that is divided into two sessions, due to the limited classrooms, facilities and lack of educators, resulting in the achievement of educational muu is not optimal. The role of youth in minimizing educational discrimination in remote communities, especially at SD Inpres 5 Bahong Langi, is by providing donations in the form of reading books, school uniforms, the Qur'an, writing books and manifesting themselves as educators for a while. In addition, another role carried out is to be an extension of the community in conveying aspirations so that the school receives more attention from the government.